Information and Communication Technology in Teaching and Learning among Islamic Education Teachers: The Roles - Wan Ismail, Wan Abdullah; Abdulsoma, Thoarlim; Abdul Hakim, Abdullah; Daud, Ismail; Razi, Yaakob (2016)
The aim of this study is to investigate the level of knowledge of Islamic Education Teachers Teaching Graduate Program UniSZA on the role of information and communication technology applied in their teaching and learning activities. The respondents consisted of Islamic Education teachers who are currently enrolled in Teaching Graduate Program at UniSZA and the samples of the study have involved 230 of respondents. Data was collected by using a questionnaire and was constructed to test the roles of Information and Communication Technology applied in teaching and learning activities that engage respondents. Data were analyzed by using the Statistical Package for Social Science v.22 for Windows (SPSS) to obtain mean and percentage frequency. Reliability of item questionnaires was obtained based on a pilot study conducted prior to the actual survey. The results of the pilot study reliability for the item level use of Information and Communication Technology is .87. The results of descriptive statistical analysis showed a HIGH consumption level of roles about information and communication technology among respondents involved in this study. The quality of services among teachers and student’s academic achievement can be improved when Information and Communication Technology were used in teaching and learning activities.